The efficacy of topical 0.1% mometasone furoate for treating symptomatic severe phimosis: A comparison of two treatment regimens - Zhou, Guanglun; Yin, Jianchun; Sun, Junjie; Zhu, Wenbin; Jin, Shiyang; Li, Shou-lin (Frontiers in Pediatrics, 2022)
Background: Twice daily 0.1% mometasone furoate is an effective treatment for phimosis in children. However, mometasone furoate has an important therapeutic advantage because it is effective in once-daily applications. This study was to compare the efficacy of two different topical 0.1% mometasone furoate regimens for the treatment of symptomatic severe phimosis in pediatric patients. Methods: A total of 1689 patients with symptomatic severe phimosis classified by the Kikiros system were prospectively enrolled in the study from March 2018 to February 2021. A total of 855 patients received 0.1% mometasone furoate twice-daily (BID group) and 834 patients received 0.1% mometasone furoate once-daily (QD group) for 4 weeks. Results: A total of 1595 boys completed the treatment (798 and 797 in the BID and QD groups, respectively). The success rate of the BID group was higher than that of the QD group at the end of week 2 (44.8% vs 33.3%, P < 0.05), while there was no difference in the success rate at 4 weeks and 3 months between the two groups (70.7% vs 69.7%, and 66.8% vs 64.9%, respectively) (P > 0.05). In both treatment groups, the success rate of grade 5 phimosis was lower than that of grade 4 at 2 weeks, 4 weeks, and 3 months. A total of 83 patients experienced recurrence of phimosis. Only fifteen patients had local mild adverse drug reactions. Conclusion: Topical application of 0.1% mometasone furoate once-daily or twice-daily for 4 weeks had comparable efficacy in children with symptomatic severe phimosis. A once a day regimen may be more suitable for children. Topical steroid application is more effective in children with low-grade phimosis than those with high-grade phimosis.